Factors influencing choices of empirical antibiotic treatment for bacterial infections in a scenario-based survey in Vietnam - Vu, TLH; Vu, QD; Hoang, BL; Nguyen, TCT; Ta, TDN; Nadjm, B; van Doorn, HR (Oxford University Press, 2020)
Background Antimicrobial stewardship (AMS) programmes have been implemented around the world to guide rational use of antibiotics but implementation is challenging, particularly in low- and middle-income countries, including Vietnam. Understanding factors influencing doctors’ prescribing choices for empirical treatment can help design AMS interventions in these settings. Objectives To understand doctors’ choices of antibiotics for empirical treatment of common bacterial infections and the factors influencing decision-making. Methods We conducted a cross-sectional survey among medical professionals applying for a postgraduate programme at Hanoi Medical University, Vietnam. We used a published survey developed for internal medicine doctors in Canada. The survey was self-administered and included four clinical scenarios: (i) severe undifferentiated sepsis; (ii) mild undifferentiated sepsis; (iii) severe genitourinary infection; and (iv) mild genitourinary infection. Results A total of 1011/1280 (79%), 683/1188 (57.5%), 718/1157 (62.1%) and 542/1062 (51.0%) of the participants selected combination therapy for empirical treatment in scenarios 1, 2, 3 and 4, respectively. Undifferentiated sepsis (OR 1.82, 95% CI 1.46–2.27 and 2.18, 1.51–3.16 compared with genitourinary) and severe infection (1.33, 1.24–1.43 and 1.38, 1.21–1.58 compared with mild) increased the likelihood of choosing a combination therapy and a carbapenem regimen, respectively. Participants with higher acceptable minimum threshold for treatment coverage and young age were also more likely to prescribe carbapenems. Conclusions Decision-making in antibiotic prescribing among doctors in Vietnam is influenced by both disease-related characteristics and individual factors, including acceptable minimum treatment coverage. These findings are useful for tailoring AMS implementation in Vietnam and other, similar settings.